Prolonged Complete Response in a Patient with Metastatic Pancreatic Adenocarcinoma after FOLFIRINOX Chemotherapy and Maintenance with FOLFIRI - Nikolaou, Christos (Case Rep Oncol Med, 2015)
Metastatic pancreatic adenocarcinoma confers a poor prognosis. Even with recent advances in the treatment of this disease with the introduction of two modestly effective chemotherapy regimens, complete responses are still very rare. Moreover, there are no published data on how to further manage the patients who achieve a sustained remission following treatment. Herein, we report the case of a patient with metastatic pancreatic adenocarcinoma who achieved a complete response lasting for more than three years after receiving induction chemotherapy with FOLFIRINOX followed by maintenance with FOLFIRI.